Irenaeus, the scriptures, and the apostolic writings reevaluating the status of the New Testament writings at the end of the second century - Laing, Kenneth (London New York Oxford New Delhi Sydney T&T Clark, 2022)
"This book challenges the customary view of Irenaeus' conception of the nature and authority of the New Testament writings"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Irenaeus -- Saint, Bishop of Lyon; Bible -- Criticism, interpretation, etc; Bible -- Canon; Bible -- Evidences, authority, etc; Revelation